Increasing NBPT rates to reduce ammonia volatilization losses from urea applied over sugarcane straw - Mira, Acácio Bezerra de (2016)
Urea is the main nitrogen (N) fertilizer used worldwide, but N losses in the form of ammonia (NH3) is a major problem when this fertilizer is topdressed over crop residues. The treatment of urea with N-(n-butyl) thiophosphoric triamide (NBPT) decreases the activity of urease enzyme and volatilization losses in many crops. However, the amount of straw over the soil in green cane trash blanketing (GCTB) systems affect the effectiveness of NBPT-treated urea in reducing NH3 losses. The hypothesis of this study is that an increase of NBPT concentration in NBPT-treated urea above the commercial concentration adopted nowadays (530 mg kg-1) is necessary to reduce volatilization losses and improve the efficiency of this fertilizer in GCTB systems. The aim of this study was to evaluate, under field conditions, NH3 losses from urea amended with four NBPT concentrations and applied over sugarcane straw. Six field trials were carried out across the State of São Paulo, the main sugarcane-cropped area in Brazil. It was adopted the randomized block experimental design with four replications. The treatments consisted of urea amended with the NBPT concentrations 0, 530, 850, 1500 and 2000 mg kg-1, ammonium nitrate and a control treatment (without N fertilizer). The NH3 volatilization was measured through an enclosure semi-static collector system containing two polyethylene foam discs treated with orthophosphoric acid and glycerol. The foam discs were collected and replaced at 2, 4, 6, 8, 10, 12, 16, 20, 25 and 30 days after the fertilizer application (DAF). The N trapped into the foams was extracted using deionized water and the N concentration determined by Flow Injection Analysis (FIA). Boltzmann sigmoidal models were fitted to cumulative losses of NH3 along the days. Cumulative losses between locals were compared by Tukey HSD and the effect of NBPT concentrations were tested by regression analyses (P<0.05). There was a significant effect of local and environmental conditions on amount of NH3 losses. NBPT was less effective in reducing NH3 losses under high temperatures and thick straw layer, probably because of the high urease activity and the early inhibitor degradation. The increase on NBPT concentration on urea above 530 mg kg-1 not only delayed the time of maximum rate of loss (Tmax), but also reduced cumulative NH3 losses. The two higher NBPT concentrations promoted an average delay of six days from untreated urea Tmax. Linear reduction of NH3 emissions occurred up to the NBPT concentration of 1000 mg kg-1 that reduced 43% of NH3 losses as compared to urea. Any increment in NBPT concentration above this range did not reflect in substantial reduction of NH3 losses. Increase NBPT concentration showed potential in reducing NH3 volatilization losses under GCTB sugarcane, however, further research is necessary to evaluate the impact of NH3 savings on sugarcane yield and the economic feasibility of this technology.